Efeito de métodos de desgaste com pontas diamantadas e da ressinterização sobre o limite de fadiga flexural de uma zircônia parcialmente estabilizada por ítria - Polli, Gabriela Scatimburgo [UNESP] (2015)
The purpose of this study was evaluate the effect of grinding protocols, followed or not by resintering, on the flexural fatigue limit of the LavaTM Y-TZP (3M ESPE) ceramic. One hundred and twenty bar-shaped specimens were obtained: 20×4.0×1.2mm (n=40) and 20×4.0×1.5mm (n=80). Half of the thinner specimens constituted the as-sintered (control) group (AS), while the thicker ones were ground with diamond burs (4ZR, Komet-Brasseler) under constant irrigation (WG) or not (G). The other half of the thinner specimens, and half of the ground ones were resintered (1000ºC for 30 min), resulting in the ASR, WGR and GR groups. The samples were evaluated by the staircase method, proposed by Dixon and Mood, with the initial stress level set at 60 % of the monotonic flexural strength. Specimens were mounted in a four-point flexural fixture in artificial saliva bath at 37±1ºC, and subjected to 500,000 cycles at 10 Hz. SEM (×500) images from the tensile side of non-fractured specimens (n=3), and of non-fatigued as-sintered ones (n=3) were used to evaluate the surface topography. In addition, SEM analyses (×30 and ×100) were performed in fractured specimens of each experimental group (n=3) to determine the origin of the failures. Data from fatigue testing were statistically analyzed by 2-way ANOVA and Tukey tests (α=.05). Grinding, performed with irrigation or not, increased the fatigue limit of the non-resintered groups. There was no significant difference among the resintered groups. Resintering significantly increased the fatigue limit of AS group. Cyclic loading and resintering did not change the surface topography of zirconia. Grinding created apparent grooves on the zirconia surface. Regardless of the experimental groups, failures initiated at the tensile side of the specimens. Grinding increased the flexural fatigue limit of LavaTM Y-TZP, while resintering did not provide a significant increase in the fatigue limit of the ground specimens.